HUBUNGAN PENGETAHUAN, SIKAP BAB, DAN KEPEMILIKAN SEPTIC TANK DENGAN STATUS ODF (OPEN DEFECATION FREE) DI KECAMATAN CANDISARI KOTA SEMARANG - Hadiati Sukma Ika Pertiwi; Mursid Rahardjo; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
ODF (Open Defecation Free) is one of the conditions of a society has done a total sanitation that is not defecate carelessly. In April 2018, Candisari has the lowest percentage of ODF from 16 sub districts in Semarang City which is 28% with 14% percentage of villages verified and 14% villages with sanitation access. Theapurposeaofathisaresearchaisatoaknowathearelationshipaof defecate behavior, defecate attitude, and avaiblability of septic tank. This research is analytic observational research with cross sectional study design. Total population on this research is 22.455 Heads of Families with 67 samples. Dataaanalysisausingaunivariateaandabivariate analysis withaChi Square statistical test (significance level=0.05). Respondents with good knowledge (56.7%), positive defecate attitude (50.7%), and have a septic tank (25.4%). The Chi Square test shows that there is correlationabetweenaknowledge of respondent (p=0.029), defecate attitude of respondent (p=0.000), and avaibility of septic tank (0.000) with ODF status. From this research, there is correlation between knowledge, defecate attitude and avaibility of septic tank with ODF status in Candisari sub district.